2012
DOI: 10.1016/j.jpain.2011.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Smoking Cigarettes as a Coping Strategy for Chronic Pain Is Associated With Greater Pain Intensity and Poorer Pain-Related Function

Abstract: Smoking cigarettes is prevalent among individuals with chronic pain. Some studies indicate nicotine reduces pain and others suggest it may cause or exacerbate pain. Participants in this cross-sectional study were 151 chronic pain patients from a large, urban VA medical center. Patients were divided into 3 groups: (1) non-smokers, (2) smokers who deny using cigarettes to cope with pain, and (3) smokers who report using cigarettes to cope with pain. Patients who reported smoking as a coping strategy for chronic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
70
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(78 citation statements)
references
References 55 publications
7
70
0
1
Order By: Relevance
“…These properties of smoking are used by patients with FM as a pain coping strategy [17]. In the present study, we observed a gradually increasing prevalence of smokers in parallel with increasing TP counts (Figure 1).…”
Section: Resultssupporting
confidence: 69%
“…These properties of smoking are used by patients with FM as a pain coping strategy [17]. In the present study, we observed a gradually increasing prevalence of smokers in parallel with increasing TP counts (Figure 1).…”
Section: Resultssupporting
confidence: 69%
“…78 These factors could all contribute to the increased (2Â ) risk for PTSD among tobacco users, 79 as well as the increased risk for CP in PTSD. 80,81 It will thus be important to take into account variable contributing factors from multiple domains in the pathophysiology of PTSD 11 when considering risk for particular comorbid CP conditions. Fibromyalgia provides a good example.…”
Section: Immune System Factors In Chronic Pain and Ptsdmentioning
confidence: 99%
“…For example, smokers with chronic pain reliably endorse smoking cigarettes in response to painful episodes (Hooten, Vickers, et al, 2011; Jamison et al, 1991; Patterson et al, 2012). Data derived from ecological momentary assessment and experimental research paradigms further indicate that the experience of pain can increase urge to smoke and function as a proximal antecedent of smoking behavior (Dhingra et al, 2014; Ditre & Brandon, 2008), especially when individuals hold expectations for nicotine/tobacco-related pain reduction (Ditre, Heckman, Butts, & Brandon, 2010).…”
Section: Bidirectional Relations Between Pain and Tobacco Smokingmentioning
confidence: 99%